Balancing Cardiovascular Health: Assessing the Impact of Physical Activity on Athletic Cardiac Adaptations and Cardiac Pathology - Izabela Hądzlik; Jan Piotrowski; Julia Biały-Karbowniczek; Katarzyna Słychan; Aleksandra Jędrasek; Klaudia Bulska; Tomasz Jędrasek; Blanka Łuczak; Julia Pogoda; Konrad Sławek (Nicolaus Copernicus University in Toruń, 2024)
Physical activity is an effective therapy for preventing and treating cardiovascular diseases.   However, studies show a curvilinear relationship between exercise and survival, with diminishing returns beyond optimal fitness levels. Extreme athletic training can harm some individuals, as long-term training in professional athletes can lead to Athlete's Heart Syndrome (AHS), characterized by structural heart changes and altered cardiac conduction due to high-intensity exercise. Intense exertion also increases the risk of sudden cardiac death by exacerbating underlying cardiac conditions. A step-by-step multimodality approach, starting with personal and family history, clinical evaluation, and 12-lead ECG, followed by further investigations like exercise testing, echocardiography, 24-hour ECG Holter monitoring, cardiac MRI, CT, nuclear scintigraphy, or genetic testing, is essential for differentiating between extreme physiological adaptations and cardiac pathology. In this process, cardiovascular imaging is crucial for identifying structural abnormalities in athletes within the grey zone between normal adaptations and early cardiovascular disease.